Z badań nad pisemnymi sprawdzianami polonistycznymi = From Researches on Teacher's Written Tests on Polish Studies - Patrzałek, Tadeusz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
In his paper the author describes his researches on teachers' tests on Polish studies, reserarches, he undertook in Poland for the firts time. The basic materials of the researches were tests published in our country in the years 1971 to 1975 with the purpose to give answers to three fundamental questions: How often do teachers of Polish apply tests for estimation'? What are their characteristics in comparison with the requirements of up-to-date test theories? Which kind of accomplishments of the pupils are tested?
Keywords: język polski - nauczanie; testy